Bismuth ferrite-barium titanate ceramic with piezoelectric coefficient temperature stability and preparation method thereof

By introducing Ce4+ dopants and rapid quenching technology into bismuth ferrate-barium titanate ceramics, the problems of unstable piezoelectric coefficient and excessive oxygen vacancy at high temperatures are solved, and the temperature stability and depolarization performance of the ceramics are improved.

CN119751037AActive Publication Date: 2025-04-04CENT SOUTH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411950170.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Bismuth ferrate-barium titanate ceramics have problems such as unstable piezoelectric coefficient, excessive oxygen vacancy and phase structure transformation at high temperatures, which limits their application in high temperature environments.

Method used

By introducing the ion dopant Ce4+ in bismuth ferrate-barium titanate ceramic, replacing Ba2+, and introducing excess free positive charge (holes) to compensate for the oxygen vacancies formed by Fe3+ at high temperatures, and combining rapid quenching technology, the generation of oxygen vacancies and the transformation of phase structure are inhibited.

Benefits of technology

The piezoelectric coefficient of bismuth ferrate-barium titanate ceramics is maintained stable within a certain temperature range, which improves the temperature stability of its piezoelectric performance, and extends the depolarization starting temperature, which is suitable for high-temperature piezoelectric sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751037A_ABST
    Figure CN119751037A_ABST
Patent Text Reader

Abstract

The invention relates to a bismuth ferrite-barium titanate ceramic with piezoelectric coefficient temperature stability and a preparation method thereof, the chemical formula of the bismuth ferrite-barium titanate ceramic is 0.75 BiFeO3-0. 25Ba (1-x) CexTiO3 + ywt.% MnO2, 0 < = x < = 0.05, 0 lt, 0 < = y < = 0.75, 0 < = y < = 0.05, 0 lt, 0 < = y < = 0.75, 0 < = y < = 0.05, 0 < And y < = 0.5. According to the bismuth ferrite-barium titanate ceramic provided by the invention, Ce < 4 + > with a higher ion valence state is selected for donor doping, redundant free positive charges (holes) are introduced after Ba < 2 + > is replaced, the positive charges can compensate positively charged oxygen vacancies formed by reducing Fe < 3 + > into Fe < 2 + > at a high temperature, so that generation of the oxygen vacancies is inhibited, and then rapid quenching is combined, so that the bismuth ferrite-barium titanate ceramic is prepared. The piezoelectric coefficient of the bismuth ferrite-barium titanate ceramic is kept stable within a certain temperature range, and the temperature stability of the piezoelectric property of the bismuth ferrite-barium titanate ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-free ferroelectric ceramics, and in particular relates to a bismuth ferrite-barium titanate ceramic with temperature stability of piezoelectric coefficient and a preparation method thereof. Background Art

[0002] Bismuth ferrite-barium titanate ceramic (BiFeO3-BaTiO3, BF-BT for short) is a lead-free piezoelectric ceramic material with a perovskite structure. It is considered to be a potential new lead-free piezoelectric ceramic material due to its good piezoelectric properties and high Curie temperature. The research and application of this material has received extensive attention in recent years, especially in high-temperature environments such as aerospace, geological exploration, petrochemicals, automotive engines and other fields.

[0003] Since one of the main matrices of bismuth ferrite-barium titanate ceramics is bismuth ferrite, this type of ceramics has some problems during sintering. For example, it is a metastable structure in the range of 447-767℃, which is easily decomposed into Bi-rich impurity phase and Fe-rich impurity phase, resulting in the frequent presence of a second phase in the ceramic, making it difficult to obtain a pure phase. At the same time, bismuth ferrite-barium titanate ceramics also have the problem of Bi volatilization and Fe-rich impurity phase at high temperatures. 3+ There are a lot of point defects such as oxygen vacancies in the ceramics. These oxygen vacancies will induce the transformation of the rhombohedral phase in bismuth ferrite-barium titanate from R3c to R3m phase structure at high temperature, and the degree of oxygen octahedral distortion will be reduced, and the restriction effect on ferroelectric domain will be weakened, causing the increase of piezoelectric coefficient. Therefore, the existence of these defects is not conducive to the stability of the composition and structure of BF-BT solid solution at high temperature, which greatly limits its practical application in high temperature environment.

[0004] The patent (CN115073159B) discloses a bismuth ferrite-barium titanate ceramic with high Curie temperature and high piezoelectric performance and a method for preparing the same by low-temperature oxygen-containing hot pressing sintering. The bismuth ferrite-barium titanate ceramic prepared by low-temperature oxygen-containing hot pressing sintering has a piezoelectric coefficient d of 315°C at the highest temperature. 33 Reached 498pC / N.

[0005] The patent (CN115073160B) discloses a hot pressing sintering method for preparing bismuth ferrite-barium titanate ceramics with micro-nano electric domain structure. The bismuth ferrite-barium titanate ceramics prepared by sintering aids and hot pressing repeated "hammering" process have a piezoelectric coefficient d of 360°C at the highest temperature. 33 Reached 502pC / N.

[0006] The patent (CN115093212B) discloses a high-performance bismuth ferrite-barium titanate ceramic with a use temperature exceeding 300°C and a low-temperature liquid phase sintering preparation method thereof. The piezoelectric coefficient d of the prepared bismuth ferrite-barium titanate ceramic is 360°C at the highest temperature point. 33 More than 400pC / N.

[0007] However, the piezoelectric coefficient (d 33 ) at high temperature is higher than that at room temperature 33 It has been improved by 2-3 times, but has relatively poor temperature stability, which is not conducive to the high-temperature piezoelectric sensor to maintain stable signal output within the operating temperature range. Summary of the invention

[0008] In view of the shortcomings of the prior art, the first object of the present invention is to provide a bismuth ferrite-barium titanate ceramic with temperature stability of the piezoelectric coefficient. The piezoelectric coefficient of the bismuth ferrite-barium titanate ceramic provided by the present invention remains stable within a certain temperature range, and its piezoelectric performance has excellent temperature stability.

[0009] The second object of the present invention is to provide a method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient. The preparation process of the present invention is simple and controllable.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] The present invention discloses a bismuth ferrite-barium titanate ceramic with temperature stability of piezoelectric coefficient, wherein the chemical formula of the bismuth ferrite-barium titanate ceramic is: 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2, where 0≤x≤0.05, 0 <y≤0.5。

[0012] The bismuth ferrite-barium titanate ceramic provided by the present invention uses Ce with a higher ion valence. 4+ Perform "donor" doping to replace Ba 2+ After that, excess free positive charges (holes) will be introduced, which can compensate for the positive charge caused by Fe 3+ Reduction to Fe 2+ The positively charged oxygen vacancies formed inhibit the generation of oxygen vacancies. The defect reaction equation is as follows:

[0013]

[0014] The reduction in oxygen vacancy content greatly reduces the dielectric loss of bismuth ferrite-barium titanate ceramics and increases the resistivity, thereby increasing the polarization efficiency of the ceramics and thus improving the piezoelectric performance.

[0015] In a preferred embodiment, the chemical formula of the bismuth ferrite-barium titanate ceramic is: 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2, wherein 0.005≤x≤0.05, 0.10≤y≤0.15.

[0016] Further preferably, the chemical formula of the bismuth ferrite-barium titanate ceramic is: 0.75BiFeO3-0.25Ba 1- x Ce x TiO3+y wt.%MnO2, wherein 0.01≤x≤0.05, 0.10≤y≤0.15.

[0017] More preferably, the chemical formula of the bismuth ferrite-barium titanate ceramic is: 0.75BiFeO3-0.25Ba 1- x Ce x TiO3+y wt.%MnO2, wherein 0.01≤x≤0.02, 0.10≤y≤0.15.

[0018] The invention discloses a method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient. The method comprises the following steps: according to the chemical formula of the bismuth ferrite-barium titanate ceramics, various oxide raw materials are mixed to obtain mixed powder, the mixed powder is pre-fired to obtain pre-fired powder, the pre-fired powder is granulated to obtain pellets, the pellets are pressed to obtain green bodies, the green bodies are sequentially debinded and sintered, and then quenched in cooling water to obtain the bismuth ferrite-barium titanate ceramics.

[0019] The preparation method provided by the present invention quenches the sintered blank after sintering is completed. During the quenching and cooling process, the migration time of oxygen atoms can be greatly shortened, a large number of oxygen atoms are "frozen" at sites with higher symmetry, and the distortion degree of oxygen octahedron in its rhombohedral phase unit cell is significantly weakened. This will lead to the suppression of the phase structure transformation of bismuth ferrite-barium titanate ceramics during the heating process, that is, the degree of transformation from R3c to R3m phase structure is reduced, thereby reducing the increase in the piezoelectric coefficient at high temperature, and the oxygen vacancies and other defects in the ceramics are reduced under the synergistic composition of the present invention, so that the insulation resistance performance of the material is improved, thereby extending the depolarization starting temperature of the material.

[0020] The preferred solution is based on 0.75BiFeO3-0.25Ba 1-x Ce x The elements in TiO3+y wt.%MnO2 are Fe2O3, BaCO3, CeO2, TiO2 and MnO2 in a stoichiometric ratio, and Bi2O3 is prepared with an excess of 3 mol% of Bi element.

[0021] In a preferred embodiment, the mixing method is wet ball milling, the ball milling medium is anhydrous ethanol, and the ball milling time is 4 to 8 hours.

[0022] In the actual operation process, the mixture obtained after wet ball milling was dried in an oven at 70° C. for 12 h, and passed through a 40-mesh sieve to obtain a mixed powder.

[0023] In a preferred embodiment, the pre-sintering temperature is 750-820°C, the pre-sintering time is 3-6 hours, and the heating rate is 5-15°C / min. In the actual operation, the mixed powder is then placed in an alumina crucible, compacted and covered, and then placed in a muffle furnace for pre-sintering to synthesize the main crystal phase, and then taken out for use after cooling to room temperature in the furnace.

[0024] In a preferred embodiment, the calcined powder is ground and passed through a 100-200 mesh sieve, PVB is added as a binder, and anhydrous ethanol is used as a medium for stirring and granulation to obtain granules, wherein the mass fraction of PVB in the granules is 1% to 5%.

[0025] Preferably, the pressure of the compression molding is 100-200 MPa.

[0026] In a preferred embodiment, the debinding temperature is 400-600°C, the debinding time is 2-8 hours, and the heating rate is 1-5°C / min. The PVB binder is removed by debinding, and after debinding is completed, the furnace is cooled to room temperature.

[0027] In a preferred embodiment, the sintering is carried out in an oxygen atmosphere, and the sintering process is: heating to 980-1020°C at a heating rate of 5-15°C / min, keeping the temperature for 3-6 hours, and then taking it out of the furnace immediately after the end of the heat preservation, and placing it in cooling water for quenching.

[0028] Further preferably, the temperature of the cooling water is room temperature.

[0029] Beneficial Effects

[0030] The bismuth ferrite-barium titanate ceramic provided by the present invention uses Ce with a higher ion valence. 4+ Perform "donor" doping to replace Ba 2+ After that, excess free positive charges (holes) will be introduced, which can compensate for the positive charge caused by Fe 3+ Reduction to Fe 2+The positively charged oxygen vacancies formed inhibit the generation of oxygen vacancies. The reduction in oxygen vacancy content greatly reduces the dielectric loss of bismuth ferrite-barium titanate ceramics and increases the resistivity, thereby increasing the polarization efficiency of the ceramics, thereby improving the piezoelectric performance. Combined with quenching the sintered blank, the migration time of oxygen atoms can be greatly shortened during the quenching and cooling process. A large number of oxygen atoms are "frozen" at sites with higher symmetry, and the degree of distortion of oxygen octahedrons in the rhombohedral phase unit cell is significantly weakened. This will lead to the suppression of the phase structure transformation of bismuth ferrite-barium titanate ceramics during the heating process, that is, the degree of transformation from R3c to R3m phase structure is reduced, thereby reducing the increase in the piezoelectric coefficient at high temperatures. 。

[0031] The invention adopts a combination of rapid quenching and ion doping to keep the piezoelectric coefficient of bismuth ferrite-barium titanate ceramic stable within a certain temperature range, thereby improving the temperature stability of its piezoelectric performance.

[0032] The present invention breaks through the limitation of existing bismuth ferrite-barium titanate ceramics that the piezoelectric properties fluctuate greatly with temperature, reduces the fluctuation of the piezoelectric coefficient with temperature while ensuring that the ceramics have excellent piezoelectric properties and a high Curie temperature, improves the temperature stability of the piezoelectric coefficient, and does not depolarize below the Curie temperature, providing a new choice of piezoelectric ceramic materials for high-temperature piezoelectric sensors with stable signal output. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Example 1: (a) In situ d 33 Test results; (b) non-in-situ 33 Test results.

[0034] Figure 2 Example 2: (a) In situ d of the bismuth ferrite-barium titanate ceramic obtained 33 Test results; (b) ex situ 33 Test results.

[0035] Figure 3 Example 3: (a) In situ d of the bismuth ferrite-barium titanate ceramic obtained 33 Test results; (b) non-in-situ 33 Test results.

[0036] Figure 4 In-situ d of the bismuth ferrite-barium titanate ceramic obtained in Comparative Example 1 33 Test results.

[0037] Figure 5 In-situ d of the bismuth ferrite-barium titanate ceramic obtained in Comparative Example 2 33 Test results. DETAILED DESCRIPTION

[0038] Example 1

[0039] According to the chemical formula 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2 is prepared, wherein x=0.01, y=0.15;

[0040] The mixed powder was ball-milled with anhydrous ethanol for 6 hours, taken out and placed in an oven to dry at 70°C for 12 hours, passed through a 40-mesh sieve, and then placed in an alumina crucible, compacted and covered. The mixture was then placed in a muffle furnace and heated to 800°C at a heating rate of 10°C / min for pre-sintering. The mixture was kept warm for 4 hours to synthesize the main crystalline phase. The mixture was cooled to room temperature in the furnace and taken out for use.

[0041] The pre-sintered powder was fully ground and passed through a 100-mesh sieve. 3% PVB powder by mass was added as a binder and stirred and granulated with anhydrous ethanol as a medium. The powder was dry-pressed at a pressure of 200 MPa in a powder tablet press to obtain a disc-shaped green body with a diameter × height of 10 mm × 1 mm.

[0042] The formed disc green body is placed in a tubular furnace, heated to 400℃ at a heating rate of 2℃ / min for debinding, kept at this temperature for 2h, the PVB binder is removed, and the disc is cooled to room temperature with the furnace. Then, oxygen is passed through and heated to 1000℃ at a heating rate of 10℃ / min for sintering, kept at this temperature for 4h, and immediately taken out of the furnace after the end of the heat preservation, and placed in cold water for quenching.

[0043] The surface of the sintered disc sample was polished into a thin sheet with two flat surfaces and a thickness of 0.6 mm. Silver electrodes were plated on the polished ceramic sheet. After silver was fired at 850°C for 15 minutes, it was immediately taken out of the furnace. The silver-fired ceramic sheet was polarized in silicone oil with a polarization electric field of 60 kV / cm, a polarization electric field direction perpendicular to the radial direction of the disc, a polarization temperature of 120°C, a polarization time of 30 minutes, and a voltage increase rate of 2 V / s. After being taken out, it was left to stand at room temperature and in air for 48 hours.

[0044] Sample d at room temperature 33 110.2pC / N, k p =0.37, Q m =159,ε r =425,tanδ=0.01,T C =577℃. In situ d 33 The test results show that the maximum d 33 is 142.6pC / N, which is lower than room temperature. 33 The value increases by about 29.4%. The depolarization starting temperature is 300℃. 33The test results show that in the range of 25-575℃ 33 The decline rate does not exceed 5%. Figure 1 .

[0045] Example 2

[0046] According to the chemical formula 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2 are prepared, wherein x=0, y=0.15; the mixed powder is ball-milled with anhydrous ethanol as the medium for 6 hours, taken out and placed in an oven to dry at 70°C for 12 hours, passed through a 40-mesh sieve, then placed in an alumina crucible for compaction and cover, and then placed in a muffle furnace for pre-sintering at a heating rate of 10°C / min to 800°C, kept warm for 4 hours, synthesized the main crystal phase, and taken out for standby after cooling to room temperature with the furnace. The pre-sintered powder is fully ground, passed through a 100-mesh sieve, 3% PVB powder is added as a binder, and stirred and granulated with anhydrous ethanol as the medium, and dry-pressed at a pressure of 200MPa in a powder tablet press to obtain a disc-shaped green body with a diameter×height of 10mm×1mm. The formed disc green body is placed in a tube furnace, heated to 400℃ at a heating rate of 2℃ / min for debinding, kept warm for 2h, PVB binder is removed, and cooled to room temperature with the furnace. Then, oxygen is passed through and heated to 1000℃ at a heating rate of 10℃ / min for sintering, kept warm for 4h, and immediately removed from the furnace after the end of the insulation, and placed in cold water for quenching. The surface of the sintered disc sample is polished into a thin sheet with two flat surfaces and a thickness of 0.6mm. Silver electrodes are plated on the polished ceramic sheet, and silver is burned at 850℃ for 15min and immediately removed from the furnace. The ceramic sheet after silver burning is polarized in silicone oil, with a polarization electric field of 60kV / cm, the polarization electric field direction is perpendicular to the radial direction of the disc, the polarization temperature is 120℃, the polarization time is 30min, and the voltage increase rate is 2V / s. After being taken out, it is left to stand in the air at room temperature for 48h.

[0047] Sample d at room temperature 33 107.7pC / N, k p =0.36, Q m =161,ε r =437, tanδ=0.016, T C =581°C. In situ d 33 The test results show that the maximum d 33 is 144.8pC / N, which is lower than room temperature. 33 The value increased by about 37.5%. The depolarization starting temperature was 263℃. 33 The test results show that in the range of 25-575℃ 33 The decline rate does not exceed 5%. Figure 2 .

[0048] Example 3

[0049] According to the chemical formula 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2 are prepared, wherein x=0.05, y=0.15; the mixed powder is ball-milled with anhydrous ethanol as the medium for 6 hours, taken out and placed in an oven to dry at 70°C for 12 hours, passed through a 40-mesh sieve, then placed in an alumina crucible for compacting and covering, and then placed in a muffle furnace for pre-sintering at a heating rate of 10°C / min to 800°C, kept warm for 4 hours, synthesized the main crystal phase, and taken out for standby after cooling to room temperature with the furnace. The pre-sintered powder is fully ground, passed through a 100-mesh sieve, 3% PVB powder is added as a binder, and stirred and granulated with anhydrous ethanol as the medium, and dry-pressed at a pressure of 200MPa in a powder tablet press to obtain a disc-shaped green body with a diameter×height of 10mm×1mm. The formed disc green body is placed in a tube furnace, heated to 400℃ at a heating rate of 2℃ / min for debinding, kept warm for 2h, PVB binder is removed, and cooled to room temperature with the furnace. Then, oxygen is passed through and heated to 1000℃ at a heating rate of 10℃ / min for sintering, kept warm for 4h, and immediately removed from the furnace after the end of the insulation, and placed in cold water for quenching. The surface of the sintered disc sample is polished into a thin sheet with two flat surfaces and a thickness of 0.6mm. Silver electrodes are plated on the polished ceramic sheet, and silver is burned at 850℃ for 15min and immediately removed from the furnace. The ceramic sheet after silver burning is polarized in silicone oil, with a polarization electric field of 60kV / cm, the polarization electric field direction is perpendicular to the radial direction of the disc, the polarization temperature is 120℃, the polarization time is 30min, and the voltage increase rate is 2V / s. After being taken out, it is left to stand in the air at room temperature for 48h.

[0050] Sample d at room temperature 33 73.3pC / N, k p =0.23, Q m =65,ε r =530, tanδ=0.036, T C =602℃. In situ d 33 The test results show that the maximum d 33 is 149.5pC / N, which is lower than room temperature. 33 The value increased by about 104%. The depolarization starting temperature was 315℃. 33 The test results show that in the range of 25-150℃ 33 The decline rate does not exceed 5%. Figure 3 .

[0051] Comparative Example 1

[0052] According to the chemical formula 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2 are prepared, wherein x=0.01, y=0.15; the mixed powder is ball-milled with anhydrous ethanol as the medium for 6 hours, taken out and placed in an oven to dry at 70°C for 12 hours, passed through a 40-mesh sieve, then placed in an alumina crucible for compaction and cover, and then placed in a muffle furnace for pre-sintering at a heating rate of 10°C / min to 800°C, kept warm for 4 hours, synthesized the main crystal phase, and taken out for standby after cooling to room temperature with the furnace. The pre-sintered powder is fully ground, passed through a 100-mesh sieve, 3% PVB powder is added as a binder, and stirred and granulated with anhydrous ethanol as the medium, and dry-pressed at a pressure of 200MPa in a powder tablet press to obtain a disc-shaped green body with a diameter×height of 10mm×1mm. The formed disc green body is placed in a tube furnace, heated to 400℃ at a heating rate of 2℃ / min for debinding, kept warm for 2h, PVB binder is removed, and the sample is cooled to room temperature with the furnace. Then, oxygen is passed through and heated to 1000℃ at a heating rate of 10℃ / min for sintering, kept warm for 4h, and cooled to room temperature with the furnace. The surface of the sintered disc sample is polished into a thin sheet with two flat surfaces and a thickness of 0.6mm. Silver electrodes are plated on the polished ceramic sheet. After silver is burned at 850℃ for 15min, it is immediately taken out of the furnace. The ceramic sheet after silver burning is polarized in silicone oil, with a polarization electric field of 60kV / cm, the polarization electric field direction is perpendicular to the radial direction of the disc, the polarization temperature is 120℃, the polarization time is 30min, and the voltage increase rate is 2V / s. After being taken out, it is left to stand in the air at room temperature for 48h.

[0053] Sample d at room temperature 33 105.3pC / N, k p =0.36, Q m =131,ε r =450, tanδ=0.021, T C =557℃. In situ d 33 The test results show that the maximum d 33 is 192.5pC / N, which is lower than room temperature. 33 The value increased by about 80%. Figure 4 .

[0054] Comparative Example 2

[0055] According to the chemical formula 0.75BiFeO3-0.25Ba 1-x Ce xTiO3+y wt.%MnO2 are prepared, wherein x=0, y=0.05, 0.15 and 0.30; the mixed powder is ball-milled with anhydrous ethanol as the medium for 6 hours, taken out and placed in an oven to dry at 70°C for 12 hours, passed through a 40-mesh sieve, then placed in an alumina crucible for compacting and covering, and then placed in a muffle furnace for pre-sintering at a heating rate of 10°C / min to 800°C, kept warm for 4 hours, synthesized the main crystal phase, and taken out for standby after cooling to room temperature with the furnace. The pre-sintered powder is fully ground, passed through a 100-mesh sieve, 3% PVB powder is added as a binder, and stirred and granulated with anhydrous ethanol as the medium, and dry-pressed at a pressure of 200MPa in a powder tablet press to obtain a disc-shaped green body with a diameter×height of 10mm×1mm. The formed disc green body is placed in a tube furnace, heated to 400℃ at a heating rate of 2℃ / min for debinding, kept warm for 2h, PVB binder is removed, and the sample is cooled to room temperature with the furnace. Then, oxygen is passed through and heated to 1000℃ at a heating rate of 10℃ / min for sintering, kept warm for 4h, and cooled to room temperature with the furnace. The surface of the sintered disc sample is polished into a thin sheet with two flat surfaces and a thickness of 0.6mm. Silver electrodes are plated on the polished ceramic sheet, and the silver is fired at 850℃ for 15min and then immediately removed from the furnace. The ceramic sheet after silver firing is polarized in silicone oil, with a polarization electric field of 60kV / cm, a polarization electric field direction perpendicular to the radial direction of the disc, a polarization temperature of 120℃, a polarization time of 30min, and a voltage increase rate of 2V / s. After being taken out, it is left to stand in the air at room temperature for 48h.

[0056] Sample d at room temperature 33 They are 99.7pC / N, 104.6pC / N and 94.3pC / N respectively. 33 The test results show that the maximum d 33 They are 144.7pC / N, 184.6pC / N and 203.3pC / N respectively, which are lower than room temperature d 33 The values ​​increased by about 44.3%, 76.5% and 113.5% respectively. The depolarization starting temperatures were 243℃, 325℃ and 317℃ respectively. Figure 5 .

Claims

1. A bismuth ferrite-barium titanate ceramic with temperature stability of piezoelectric coefficient, characterized in that: The chemical formula of the bismuth ferrite-barium titanate ceramic is: 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2, where 0≤x≤0.05, 0 <y≤0.5。 2. The bismuth ferrite-barium titanate ceramic with temperature-stable piezoelectric coefficient according to claim 1, characterized in that: The chemical formula of the bismuth ferrite-barium titanate ceramic is: 0.75BiFeO3-0.25Ba 1-x Ce x TiO3+y wt.%MnO2, wherein 0.005≤x≤0.05, 0.10≤y≤0.

15.

3. The method for preparing a bismuth ferrite-barium titanate ceramic with temperature stability of piezoelectric coefficient according to claim 1 or 2, characterized in that: According to the chemical formula of bismuth ferrite-barium titanate ceramics, various oxide raw materials are mixed to obtain mixed powder, the mixed powder is pre-fired to obtain pre-fired powder, the pre-fired powder is granulated to obtain pellets, the pellets are pressed to obtain green bodies, the green bodies are successively debinded and sintered, and then quenched in cooling water to obtain bismuth ferrite-barium titanate ceramics.

4. The method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient according to claim 3, characterized in that: According to 0.75BiFeO3-0.25Ba 1-x Ce x The elements in TiO3+y wt.%MnO2 are Fe2O3, BaCO3, CeO2, TiO2 and MnO2 in a stoichiometric ratio, and Bi2O3 is prepared with an excess of 3 mol% of Bi element.

5. The method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient according to claim 3, characterized in that: The mixing method is wet ball milling, the ball milling medium is anhydrous ethanol, and the ball milling time is 4 to 8 hours.

6. The method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient according to claim 3, characterized in that: The pre-firing temperature is 750-820° C., the pre-firing time is 3-6 hours, and the heating rate is 5-15° C. / min.

7. The method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient according to claim 3, characterized in that: The pre-sintered powder is ground and passed through a 100-200 mesh sieve, PVB is added as a binder, and anhydrous ethanol is used as a medium for stirring and granulation to obtain granules, wherein the mass fraction of PVB in the granules is 1%-5%.

8. The method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient according to claim 3, characterized in that: The pressure of the compression molding is 100-200 MPa.

9. The method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient according to claim 3, characterized in that: The debinding temperature is 400-600° C., the debinding time is 2-8 hours, and the heating rate is 1-5° C. / min.

10. The method for preparing bismuth ferrite-barium titanate ceramics with temperature stability of piezoelectric coefficient according to claim 3, characterized in that: The sintering is carried out in an oxygen atmosphere. The sintering process is: heating to 980-1020° C. at a heating rate of 5-15° C. / min, keeping the temperature for 3-6 hours, and immediately taking it out of the furnace after the end of the heat preservation, and placing it in cooling water for quenching.

Citation Information

Patent Citations

  • Bismuth sodium titanate based leadless piezoelectric ceramic

    CN101234895A

  • Perovskite leadless piezoelectric ceramic used at high temperature and preparation method thereof

    CN102584194A

  • Bismuth ferrite-barium titanate lead-free piezoelectric ceramic material, preparation method and application

    CN116573928A

  • Piezoelectric ceramic composition and piezoelectric element

    JP2013155079A

  • Capacitative element, integrated circuit and electronic device

    US20070045595A1